Benchmarking: A way of finding risk factors in business performance - Jarmila Horváthová; Martina Mokrišová; Mária Vrábliková (Journal of Risk and Financial Management, 2021)
The purpose of this study was to emphasize that the Data Envelopment Analysis (DEA) method is an important benchmarking tool which provides necessary information for improving business performance. To fulfil the abovementioned goal, we used a sample of 48 Slovak companies involved in the field of heat supply. As their position in the economic and social environment of the country is essential, considerable attention should be paid to improving their performance. In addition to the DEA method, we applied the Best Value Method (BVM). We found that DEA is a highly important benchmarking tool, as it provides benchmarks for units that have problems with performance and helps us to reveal risk performance factors. The DEA method also allows us to determine target values of indicators. The originality of this paper is in its comparison of the results of the BVM and the DEA methods.
Keywords: 330; benchmarking; best value; business; data envelopment analysis (DEA); performance; risk factors